Ecological Justice and the Extinction Crisis Giving Living Beings their Due - Wienhues, Anna (Bristol University Press, 2020)
"ePDF and ePUB available Open Access under CC-BY-NC-ND licence. As the biodiversity crisis deepens, Anna Wienhues sets out radical environmental thinking and action to respond to the threat of mass species extinction. The book conceptualises large-scale injustice endangering non-humans, and signposts new approaches to the conservation of a shared planet. Developing principles of distributive ecological justice, it builds towards a bold vision of just conservation that can inform the work of policy makers and activists. This is a timely, original and compelling investigation into ethics in the natural world during the Anthropocene, and a call for biocentric ecological justice before it is too late."